Genesis of Identity in Scientific Thought - Ostapievsky, Alexander Igorevich (Psychological Prospects Journal, 2013)
The article deals with theoretical developments of the phenomenon of identity in scientific thought as a dynamic structure that develops during human life and defines its identity, integrity, identity and awareness of differences from other subjects.